PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE DALAM MENINGKATKAN MINAT BELAJAR DI SMPN 1 SAPE - Afrianti, Ifa; Mustamin; Sudarmono, Muh Aidil; Syahid, Akhmad; Raehana, Syarifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of the Picture and Picture learning model and increase student interest in learning in Islamic Religious Education (PAI) subjects in class VIII.K SMP Negeri 1 Sape, Bima Regency. This study is a Classroom Action Research (CAR) which was carried out in two cycles, each consisting of two meetings, with 31 students as research subjects. Data collection techniques include observation, interviews, tests, and documentation. Test instruments in the form of pre-tests and post-tests were used to measure learning outcomes, while observation sheets were used to determine student activity and involvement during learning. Data analysis was carried out by calculating percentages and average values ​​(means). The results of the study showed a significant increase in each cycle. In the pre-cycle, only 7 students completed the course with an average score of 63.22 (22.58%). In cycle I, the number of students who completed the course increased to 20 with an average score of 77.09 (64.51%). In cycle II, the improvement was more significant, with 28 students completing the task, an average score of 90.64, and a completion percentage of 90.32%. Observations also showed an increase in student activity and enthusiasm. Thus, the Picture and Picture model effectively increased student interest and learning outcomes.